Focus on HPV‑driven head and neck cancers - Villa, Luisa Lina; Sichero, Laura (Brazilian Journal of Sexually Transmitted Diseases, 2022)
A brief search on Pubmed.org reveals a continuous increase in the number of publications regarding HPV (Human Papillomavirus) in Head and Neck Cancers (HNC): from less than 10 per year in the 1990’s to over 100 in the present decade, with about 10 review articles solely in 2017! Many reasons account for such significant change, remarkably the recognition of high‑risk HPVs (mainly HPV‑16) as the etiological agent of a substantial proportion of HNC, although highly heterogeneous by cancer anatomical site, geographical region and gender. In fact, several features are being explored in diverse studies and trials around the World, which reflect on the large number of papers on the subject presented at the 31st International Papillomavirus Conference held in Cape Town (South Africa) last March. This Editorial highlight the reasons for the increased focus on HPV‑related HNC. [...]